Including Homeless Families and Children in the Social Protection System: A Brief Review of International Experience and Data on a Philippine Pilot Program - Mendoza, Ronald U (Archīum Ateneo, 2013)
The Philippines’ social protection system is anchored on the Pantawid Pamilyang Pilipino Program (4Ps). Under the management of the Department of Social and Welfare Development (DSWD), the 4Ps covered over 3 million families and about 7.5 million children for a period of 64 months (February 2008 to May 2012), helping ensure that these children will grow up to be educated, healthy, and productive members of Philippine society. Part of its program innovations and improvements to keep pace with the challenges of a rapidly growing and urbanizing economy is the launched in late 2012, the pilot program - Modified Conditional Cash Transfer for Homeless Street Families (MCCT-HSF). This program aims to provide immediate support and services (e.g. health, education, and housing grants) to homeless families with a long-term view towards empowerment to find alternatives to the harsh life on the streets, as well as integration into the 4Ps. Protecting street children from the potential harm and abuse of street life, and creating a stable environment which could eventually see them going back to school and receiving further investments in their wellbeing are also among the program objectives. The present study analyzed the key information of the MCCT-HSF beneficiaries, reviewed country experiences (in Chile, South Africa, India, and Brazil) support and services for the homeless, and determined main areas for consideration to enhance the design of the MCCT-HSF.